Analysis of Business Development of Coffee Beverage (Case Study Of Greenhouse Coffee And Meal, Denpasar) - Sulastri, Ida Ayu Inten Dwi; Merta, I Made; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
This study aimed to calculate the financial feasibility and to identify the Strengths, Weaknesses, Opportunities, and Threats (SWOT) of a coffee beverage business. Financial feasibility was analyzed using quantitative descriptive methods, including Net Present Value (NPV), Internal Rate of Return (IRR), and Break Even Point (BEP) calculations, while SWOT analysis was conducted using qualitative descriptive methods. The results showed that the coffee beverage business is highly profitable, generating a net profit of Rp. 28,600,950 per year, and is suitable for development. The financial feasibility analysis indicated an NPV of Rp. 22,280,872. Sensitivity analysis revealed that a 15% increase in operating costs and a 10% decrease in revenue did not affect the project’s feasibility. Overall, the coffee beverage business is very feasible to develop.